Advancing Analytic Halo Mass Function Models Through Large-Scale Cosmological Simulations - Miao, Jiaye (Transactions on Computer Science and Intelligent Systems Research, 2025)
We develop an analytic halo mass function (HMF) framework calibrated on the comprehensive Abacus-Summit simulations, achieving 2–3% accuracy for CDM ( 5% for extended cosmologies with massive neutrinos, evolving dark energy, and modified power spectra) across and . Unlike universal forms limited to CDM, our MCMC-optimized model explicitly incorporates redshift and cosmology dependence while maintaining physical interpretability. The analytic formulation enables application to new physics without costly retraining, complementing more precise but less flexible emulator-based approaches. We quantify systematic uncertainties from resolution effects, sample variance, and mass definitions, and outline future improvements through symbolic regression. This work provides a robust tool for cosmological tests with galaxy clusters and large-scale structure at percent-level precision.